Spontaneous Rupture of the Anterior Vaginal Wall during the First Stage of Labour - Meleesa Joy Schultz; Triveni Nanda (Hindawi Limited, 2012)
The risk of uterine rupture during attempted trial of labor after caesarean delivery (TOLAC) is well documented. However, vaginal rupture (in the absence of obstructed labour) is exceptionally uncommon. Below is described the rare case of a 37-year-old multiparous woman attempting TOLAC, who suffered a vaginal-rather than uterine-rupture, during the first stage of spontaneous labour. This case is an important reminder to obstetricians that concealed ruptures of both the vagina and uterus do occur and must be considered in clinical situations where another explanation is not apparent.